1987
DOI: 10.2105/ajph.77.7.866
|View full text |Cite
|
Sign up to set email alerts
|

Measles hospitalizations, United States, 1977-84: comparison with national surveillance data.

Abstract: (Am J Public Health 1987; 77:866-868.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…[10][11][12][13] However, AOM following acute measles infection has generally been considered to be caused by secondary bacterial infection and this is the first report on the isolation of measles virus from MEF in patients with AOM.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] However, AOM following acute measles infection has generally been considered to be caused by secondary bacterial infection and this is the first report on the isolation of measles virus from MEF in patients with AOM.…”
Section: Discussionmentioning
confidence: 99%
“…A key complication is otitis media, which occurs in up to 10% of individuals who have been hospitalized due to the acute infection [95][96][97]. The mechanism by which this occurs is unknown and again it could possibly be due to the virus-mediated immunosuppression, which allows opportunistic secondary infections in the middle ear by decreasing levels of IgG and IgM within this compartment.…”
Section: Hearing Loss and Measles Infectionmentioning
confidence: 99%
“…This study found increasing hospitalizations for measles in the US between 2002-2016, with prolonged and costly hospitalizations. The estimated total number of measles hospitalizations in the US from 1977-1984 was 13,710 [26], which increased from 1985-1996 to 28,047, driven largely by the 1989-1991 epidemic [27]. From 1996 to 2002 measles hospitalizations were at an all-time low in US history with an estimated �23 cases annually [27].…”
Section: Discussionmentioning
confidence: 99%
“…We found gastrointestinal, hematologic, infectious, neurologic, ophthalmologic, pulmonary, and renal complications in inpatients with measles. From 1977-1984, the most common complications among hospitalized patients included pneumonia or other respiratory complications (34%), otitis media (8.5%), and encephalitis/convulsions/coma (3.4%); while pneumonia and otitis media frequency decreased with age, neurologic complications increased [26]. From 1987-2000, among all cases of measles, diarrhea (8.2%), otitis media (7.3%), pneumonia (5.9%), and encephalitis (0.1%) were the most prevalent [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation